Ecological risk assessment of polycyclic aromatic hydrocarbons in surface sediments from the middle and lower reaches of the Yellow River, China. Issue 2 (17th February 2016) - Feng, Jinglan; Hu, Pengtuan; Zhang, Fei; Wu, Yufan; Liu, Shuhui; Sun, Jianhui
ABSTRACT: In this research, ecological risks for eight individual polycyclic aromatic hydrocarbons (PAHs) and ∑PAH8 in surface sediments from middle and lower reaches of Yellow River are evaluated using overlapping areas of probability density curves and margin of safety (MOS), based on the toxicity data and the exposure concentrations of PAHs in sediments collected from 23 sites. In the overlapping areas of probability density curves, the risk of Ant and Pyr are the highest, then the risk level is in the order of Flua > Nap > Phe > BaP > Flu > Ace. The values of MOS10 present that Pyr (4.62 × 10 −4 ), Ant (5.60 × 10 −3 ), and Flua (6.4 × 10 −3 ) have a significantly high ecological risk level, while Nap and Phe have middle-level ecological risk. As for Ace, BaP, and Flu, they pose limited risk to the ecological system with MOS10 greater than 1.0. The ∑PAH8 (2.66 × 10 −5 ) is a higher risk level than that of any individual PAHs, where the probabilities of ∑PAH8 in excess of the 10th percentile of the toxicity data were 86%.